2019
DOI: 10.1038/s41586-019-1609-1
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the inner kinetochore CCAN complex assembled onto a centromeric nucleosome

Abstract: In eukaryotes, accurate chromosome segregation in mitosis and meiosis maintains genome stability and prevents aneuploidy. Kinetochores are large protein complexes, that by assembling onto specialized Cenp-A nucleosomes 1,2 , function to connect centromeric chromatin to microtubules of the mitotic spindle 3,4 . Whereas the centromeres of vertebrate chromosomes comprise Mb of DNA and attach to multiple microtubules, the simple point centromeres of budding yeast are connected to individual microtubules 5,6 . All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
269
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(290 citation statements)
references
References 65 publications
17
269
4
Order By: Relevance
“…Previous studies have reported molecular structures, determined by cryo-EM or crystallography, of Ctf3-C with Mcm16/22-N from S. cerevisiae and of Ctf3-N with Mcm16/22-C from related yeast species Hu et al, 2019;Zhang et al, 2020). In cryo-EM reconstructions of the complete Ctf19c, only the Ctf3-C module is well-resolved Yan et al, 2019). The new Ctf3c model shows how these structural modules relate to each other and provides a high-resolution model of S. cerevisiae Ctf3-N with Mcm16/22-C.…”
Section: Molecular Model Of the Complete Ctf3cmentioning
confidence: 99%
“…Previous studies have reported molecular structures, determined by cryo-EM or crystallography, of Ctf3-C with Mcm16/22-N from S. cerevisiae and of Ctf3-N with Mcm16/22-C from related yeast species Hu et al, 2019;Zhang et al, 2020). In cryo-EM reconstructions of the complete Ctf19c, only the Ctf3-C module is well-resolved Yan et al, 2019). The new Ctf3c model shows how these structural modules relate to each other and provides a high-resolution model of S. cerevisiae Ctf3-N with Mcm16/22-C.…”
Section: Molecular Model Of the Complete Ctf3cmentioning
confidence: 99%
“…The extensive works have revealed the structures and functions of many CCAN components . The recent cryo‐EM structures of Saccharomyces cerevisiae CCAN complex have elucidated how the subunits are integrated into the inner kinetochore CCAN . However, further analyses are still required to clarify the detailed and dynamic interactions among the CCAN.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported the N‐terminal half structure of fungal CENP‐I that forms a ternary complex with C‐terminal heterodimer of fungal CENP‐H/K . The recent cryo‐EM structures revealed another half of Ctf3 (CENP‐I homolog), which forms complex with N‐terminal heterodimer of Mcm16/22 (CENP‐H/K homolog) . However, the intramolecular interaction and structure details of CENP‐I are less discussed.…”
Section: Introductionmentioning
confidence: 99%
“…A complementary strategy is to reconstruct kinetochore complexes using recombinant proteins, as demonstrated by the tour-de-force studies that assembled the entire linkage between human CENP-A nucleosomes, inner kinetochore components, and KMN ( Figure 1B) (Weir et al 2016, Pesenti et al 2018. In a similar vein, a recent study using recombinant Saccharomyces cerevisiae proteins demonstrated that 14 CCAN subunits have the ability to self-assemble in the presence of CENP-A nucleosomes (Yan et al 2019). Another study with yeast proteins revealed selfassembly of protein chains consisting of CENP-A nucleosomes, CENP-C and CENP-QU (Okp1/Ame1 complex) scaffolds, and the KMN components Mis12 and Ndc80 complexes (Hamilton et al 2020).…”
Section: Introductionmentioning
confidence: 99%